2014
DOI: 10.1016/j.socscimed.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure: A forgotten dimension of physical activity in older age

Abstract: Pleasure is an under-researched and under theorized concept within health and health-related areas, particularly in relation to physical activity in older age. This gap is addressed here. The paper forms part of a larger qualitative project conducted between March 2011 and July 2013 within which fifty-one physically active older adults (age sixty to ninety-two years) were interviewed about their experiences of physical activity. Twenty-seven of these participants were also involved in a photo elicitation exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 48 publications
8
130
0
2
Order By: Relevance
“…Although these microflow activities (and activity settings) may be less challenging than those facilitating peak flow, they still involve a degree of focus and are experienced as pleasurably immersive (Privette, 1983;Phoenix and Orr, 2014). As such, moments of microflow may be more widely achievable in everyday life.…”
Section: Bill: "The Fishing Is Hanging It Has Nothing Whatsoever To mentioning
confidence: 99%
“…Although these microflow activities (and activity settings) may be less challenging than those facilitating peak flow, they still involve a degree of focus and are experienced as pleasurably immersive (Privette, 1983;Phoenix and Orr, 2014). As such, moments of microflow may be more widely achievable in everyday life.…”
Section: Bill: "The Fishing Is Hanging It Has Nothing Whatsoever To mentioning
confidence: 99%
“…The results of this synthesis highlighted the importance of enjoyment to perceived improvements in well-being. Despite fun and enjoyable activities being linked to increased PA participation (Martin Ginis et al, 2016), pleasure is often the forgotten dimension of PA promotion (Phoenix & Orr, 2014). PA messages should therefore 'look beyond the usual suspects' (e.g.…”
Section: Reflectionsmentioning
confidence: 99%
“…In fact, despite reduced overall physical activity, research has found that retirement is associated with an increase in self-reported health (Coe and Zamarro 2011). Finally, physically active leisure provides a site for older adults to experience fun, pleasure, and joy, which go beyond the typical focus on physical health benefits (Phoenix and Orr 2014).…”
Section: Older Adults and Physically Active Leisurementioning
confidence: 99%